2018
DOI: 10.5812/ijpbs.12603
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Role of Mental Health Literacy in the Relationship Between Demographic Variables and Health-Promoting Behaviours

Abstract: Background: An understanding of the relationships between mental health literacy and health promotion behaviours is essential for the development of community-based interventions in the prevention of mental disorder. Objectives: The aim of this study was to examine the relationships between mental health literacy and health-promoting behaviours and to assess the contributions of mental health literacy through mediation to demographic characteristic in healthpromoting behaviours. Methods: This cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 30 publications
3
38
0
4
Order By: Relevance
“…In short, they strongly reduce the quality of life and create a considerable economic and social burden on the individual, family, and community. For this reason, management of mental disorders is one of the main priorities of health systems in different countries today, and is an issue which has attracted considerable attention from researchers and policymakers [1, 5, 6]. Due to the high prevalence, chronic nature, and long-term negative consequences of mental disorders, immediate action including continuous monitoring of the population’s mental health and designing and implementing effective control strategies, has become a urgent need in all countries [1, 3, 7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, they strongly reduce the quality of life and create a considerable economic and social burden on the individual, family, and community. For this reason, management of mental disorders is one of the main priorities of health systems in different countries today, and is an issue which has attracted considerable attention from researchers and policymakers [1, 5, 6]. Due to the high prevalence, chronic nature, and long-term negative consequences of mental disorders, immediate action including continuous monitoring of the population’s mental health and designing and implementing effective control strategies, has become a urgent need in all countries [1, 3, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a more recent revision of this concept includes the ability to provide support for someone who has a mental disorder [9]. Many studies of the concept of mental health literacy have shown that adequate mental health literacy is associated with care of the disease, information-seeking behaviour, prevention of subsequent complications, and reductions in long-term harms [5, 13]. Moreover, improved health literacy improves the use of mental health services, which in turn leads to better outcomes [4, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the Noroozi et al study showed that the Cronbach's alpha for total questions and CVR were 0.74 and 0.90, respectively [30]. In a study conducted by O'Connor, the MHLS was designed based on other questionnaires in this field, and the 55-item questionnaire was evaluated, which after psychometric evaluation of the questionnaire, finally the 35-item version of the MHLS with six substructures were confirmed and Cronbach's alpha of 0.879 and test-retest reliability of 0.797 were reported [22].…”
Section: Discussionmentioning
confidence: 96%
“…In a study by Noroozi et al, the Cronbach's alpha for total attributes of MHLS was 0.74 [35]. In a study conducted by O'Connor, the MHLS was designed based on other questionnaires in this field, and the 55-item questionnaire was evaluated, which after psychometric evaluation of the questionnaire, finally the MHLS with 35-item and six attributes were confirmed and Cronbach's alpha of 0.879 and test-retest reliability of 0.797 was reported [22].…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, this instrument seems to be useful for measuring the MHL of different age groups in society. Using this tool can be used to measure MHL and identify low literacy individuals in any attribute and design and implement intervention programs for them.In the present study, this35 items questionnaire was evaluated and modified. After evaluation of the questionnaire, 6 questions were finally omitted and the modified version of MHLS with 29 items and 6 attributes was approved.…”
mentioning
confidence: 99%